2015
DOI: 10.1155/2015/262079
|View full text |Cite
|
Sign up to set email alerts
|

Newer Classification System for Fissured Tongue: An Epidemiological Approach

Abstract: Introduction. Fissured tongue is a commonly encountered tongue disorder in dental practice. But there is a lack of data on different pattern, severity, and association of fissuring with various systemic disorders and other tongue anomalies. This study attempts to establish a classification system for fissured tongue and to know the correlation with the systemic health and other disorders of the tongue. Materials and Methods. A total of 1000 subjects between the age groups of 10 and 80 years were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 7 publications
3
33
0
6
Order By: Relevance
“…Our results are above the normal averages, and this may be attributed to the advanced age of the patients and the diagnostic variations in the studies. Based on the newer classification system for FT proposed by Sudarshan et al ., our results show that the fissuring pattern predominantly observed was of the branching and diffused types, and these were mainly associated with severe lesions. We also observed that 94% of the lesions were severe in the PS group compared to 76% in the NPS group.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results are above the normal averages, and this may be attributed to the advanced age of the patients and the diagnostic variations in the studies. Based on the newer classification system for FT proposed by Sudarshan et al ., our results show that the fissuring pattern predominantly observed was of the branching and diffused types, and these were mainly associated with severe lesions. We also observed that 94% of the lesions were severe in the PS group compared to 76% in the NPS group.…”
Section: Discussionmentioning
confidence: 63%
“…). FT was also classified according to the method proposed by Sudarshan et al ., which was based on the fissuring pattern of the tongue and the number of fissures (Figs and ). The study was approved by the Research Ethics Committee (19072613.3.0000.5243).…”
Section: Methodsmentioning
confidence: 99%
“…The etiology and pathogenesis of FT remain obscure and controversial [1,5]. FT has been associated to nutrition deficiencies, systemic diseases and syndromes [1,2,22]. Most FT epidemiological studies show a mean prevalence of 1 to 11%, usually varying with age [1,23].…”
Section: Discussionmentioning
confidence: 99%
“…There was a presence of double teeth like appearance of teeth #61 and #62 suggestive of fusion of the teeth. Other intraoral findings included narrow and deep palate (Figure ) with tongue exhibiting moderate, central transverse type fissures and macroglossia (Figure ). Clinical crown of tooth #61 and/or tooth #62 was wider mesiodistally than its normal counterpart.…”
Section: Case Descriptionmentioning
confidence: 99%